2019
DOI: 10.1371/journal.ppat.1007860
|View full text |Cite
|
Sign up to set email alerts
|

The 2nd sialic acid-binding site of influenza A virus neuraminidase is an important determinant of the hemagglutinin-neuraminidase-receptor balance

Abstract: Influenza A virus (IAV) neuraminidase (NA) receptor-destroying activity and hemagglutinin (HA) receptor-binding affinity need to be balanced with the host receptor repertoire for optimal viral fitness. NAs of avian, but not human viruses, contain a functional 2 nd sialic acid (SIA)-binding site (2SBS) adjacent to the catalytic site, which contributes to sialidase activity against multivalent substrates. The receptor-binding specificity and potentially crucial contribution of the 2SBS to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(98 citation statements)
references
References 71 publications
(140 reference statements)
3
94
0
Order By: Relevance
“…In this process, haemagglutinin (HA) mediates viral entry through binding to the cellular receptors and facilitates fusion of the virion membrane with the endosomal membrane (Byrd-Leotis et al 2017). Conversely, neuraminidase (NA) can cleave off the SAs from the cellular membrane and viral glycoproteins, facilitating the egress of nascent virions (Byrd-Leotis et al 2017;Du et al 2019). HA and NA glycoproteins collectively determine the optimal level of HA affinity and NA enzymatic cleavage to allow for productive viral infection (Byrd-Leotis et al 2017).…”
Section: Sialic Acid (Sa)mentioning
confidence: 99%
“…In this process, haemagglutinin (HA) mediates viral entry through binding to the cellular receptors and facilitates fusion of the virion membrane with the endosomal membrane (Byrd-Leotis et al 2017). Conversely, neuraminidase (NA) can cleave off the SAs from the cellular membrane and viral glycoproteins, facilitating the egress of nascent virions (Byrd-Leotis et al 2017;Du et al 2019). HA and NA glycoproteins collectively determine the optimal level of HA affinity and NA enzymatic cleavage to allow for productive viral infection (Byrd-Leotis et al 2017).…”
Section: Sialic Acid (Sa)mentioning
confidence: 99%
“…HA functions as a receptor binding and fusion protein, while the NA protein is involed in release of (nascent) virus particles from decoy receptors or the cell surface (Gamblin and Skehel, 2010;Dou et al, 2018). Recently, it has been reported that NA activity of IAV is influenced by virus-receptor binding (Guo et al, 2018;Du et al, 2019;Lai et al, 2019). NA activity is altered based on enhanced or a reduced HA-receptor binding property.…”
Section: Discussionmentioning
confidence: 99%
“…In short, IAV was incubated with CATH-B1 (0-40 µM) for 1 h at 37 • C, followed by addition of MUNANA for another 1 h at 37 • C. Next, the reaction was stopped, and fluorescence intensity was measured using a FLUOstar Omega microplate reader. The activity of NA toward the sialylated glycoprotein fetuin was analyzed in a solid phase cleavage assay using a previously described enzyme linked lectin assay (ELLA) (Dai et al, 2017;Du et al, 2019). Fetuin (2.5 ug/mL) was coated on Maxisorp Nunc 96-well plates (Thermo Fisher Scientific).…”
Section: Munana and Ella Assaymentioning
confidence: 99%
“…Different from HE, NA may do so via its catalytic pocket which doubles as a Sia-binding site 72 . However, NA also possesses a second Sia binding site 73,74 , which like the HE lectin domain, regulates NA activity and which, in further analogy, is conserved or lost in apparent correlation with host tropism 7577 . Finally, among many other similarities to embecoviruses, influenza A variants with different set points in their HA-NA functional balance may cooperate to support their propagation in cultured cells 48 .…”
Section: Discussionmentioning
confidence: 99%